Solid electrolyte with stable positive electrode interface based on perovskite, application and lithium battery
By dispersing nanotitanium dioxide and perovskite quantum dots in polyethylene oxide (PEO) matrix, the low conductivity and compatibility problems of polymer solid electrolytes are solved, the lithium ion transmission performance is improved, and the all-solid state is achieved The stable and efficient operation of lithium metal batteries.
Patent Information
- Application Number
- CN202411223312.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-03
AI Technical Summary
The existing polymer solid electrolytes have low room temperature ion conductivity and lithium ion migration number, and poor compatibility with electrode materials, which cannot meet the practical needs of all-solid lithium metal batteries.
Using a solid electrolyte with a positive interface stable interface based on perovskite, the nanotitanium dioxide particles and nanoperovskite quantum dots are uniformly dispersed in a polyethylene oxide (PEO) matrix, using Lewis acid-base action and the size of ultrafine nanoparticles. The effect reduces the proportion of crystallization zones, promotes lithium ion transport, and improves ion mobility through lithium-philicity and electrostatic adsorption of active particles.
It significantly improves the room temperature ion conductivity and lithium ion migration number, improves the compatibility of lithium metal negative electrodes, delays the growth of lithium dendrites, and ensures long-term stable circulation and efficient performance of the battery.
Smart Images

Figure CN119253027A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolyte materials, and more specifically, to a perovskite-based positive electrode interface-stabilized solid electrolyte and its application, and a lithium battery. Background Art
[0002] With the rapid consumption of fossil energy and the increasingly serious environmental pollution, clean and renewable energy such as solar energy, wind energy, tidal energy, and biomass energy are receiving more and more attention. However, due to the intermittent and variable nature of renewable energy, it is difficult to integrate the electricity generated by renewable energy into the complex load power grid. It is necessary to develop large-scale energy storage technology and corresponding mobile energy storage devices to achieve effective energy utilization. Electrochemical energy storage is an important part of energy storage technology. The way to achieve energy storage and release is the conversion between electrical energy and chemical energy. The high efficiency and high flexibility of electrochemical energy storage make its position in the field of energy storage increasingly rising. Batteries and electrochemical capacitors are currently the main devices used to complete electrochemical energy storage, and the commonly used batteries include lead-acid batteries, sodium-sulfur batteries, and lithium-ion batteries. However, due to the serious environmental pollution problems of lead-acid batteries and cadmium-nickel batteries, such as heavy metal lead, difficult-to-digest lead oxides, dust, acid mist, waste acid and other pollutants and heavy metal cadmium, they will cause considerable damage to the environment, causing unnatural phenomena such as global warming and acid rain. Lithium-ion batteries (LIBs) have many advantages such as high energy density, long service life, high working efficiency, low self-discharge and no memory effect. They play a huge role in grid energy storage as well as portable electronic devices, electric vehicles and other fields.
[0003] At present, traditional lithium-ion batteries use organic liquid electrolytes, which are easy to leak, volatile, and flammable, which lead to safety hazards such as fire and explosion in the case of short circuit or thermal runaway. Fire accidents in electric vehicles and lithium battery storage stations have been reported from time to time. On the other hand, traditional lithium batteries cannot use high-energy-density metallic lithium as the negative electrode material. During the battery cycle, due to factors such as the surface current density of metallic lithium and the uneven distribution of lithium ions, the surface of the lithium metal negative electrode will cause drastic volume changes, thereby causing continuous destruction and generation of SEI. The continuous renewal of SEI means the continuous consumption of active substances and the continuous accumulation of side reaction products, resulting in the continuous increase of battery polarization and the rapid decay of capacity.
[0004] Therefore, using solid electrolytes with high melting point / high boiling point / ignition point to replace organic liquid electrolytes and construct all-solid-state lithium batteries is expected to solve the intrinsic safety problem of lithium-ion batteries and is one of the key technical paths in the field of next-generation electrochemical energy storage that has attracted much attention. Depending on the material, solid electrolytes are generally divided into inorganic solid electrolytes and polymer solid electrolytes. Solid inorganic electrolytes have poor mechanical strength and large solid-solid interface resistance when in contact with electrodes, which has become the main obstacle to their development. Polymer solid electrolytes have many advantages such as no solvent, light weight, good flexibility, easy film formation and wide electrochemical oxidation potential. However, most of the existing polymer solid electrolytes have problems such as low room temperature ionic conductivity and lithium ion migration number and poor compatibility with electrode materials, which cannot meet practical needs. Therefore, modification research on them is of great significance for their application in the next generation of all-solid-state lithium metal batteries. Summary of the invention
[0005] In view of this, the present invention provides a perovskite-based positive electrode interface-stable solid electrolyte and its application, and a lithium battery to solve the problems of low conductivity and lithium ion migration number of polymer solid electrolytes and poor compatibility with electrode materials in the prior art.
[0006] The present invention provides a solid electrolyte with stable positive electrode interface based on perovskite, comprising: polyethylene oxide (PEO), lithium salt, nano titanium dioxide (TiO2) particles and nano perovskite quantum dots (CsPbBr X I 3-X );
[0007] The dosage of the nano titanium dioxide particles is 0.3%-0.7% of the dosage of the polyethylene oxide.
[0008] Optionally, the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide or lithium perchlorate, and the mass ratio of the lithium salt to the polyethylene oxide is 1:1-1:4.
[0009] Optionally, the nano-perovskite quantum dots include CsPbBr X I 3-X , where X is greater than 0 and less than 3.
[0010] Optionally, the dosage of nano-perovskite quantum dots is 1.0%±0.1% of polyethylene oxide.
[0011] Optionally, the perovskite-based positive electrode interface-stabilized solid electrolyte is prepared according to the following method, including:
[0012] preparing nano titanium dioxide particles;
[0013] Preparation of nano-perovskite quantum dots;
[0014] The method comprises the steps of adding polyethylene oxide powder to a lithium salt-containing solution, and then sequentially adding nano-perovskite quantum dots and nano-titanium dioxide particles, heating and stirring at 60±5° C. for 24±2 h to obtain a uniform slurry, placing the slurry in a mold to form a film, removing the solvent, and vacuum drying to obtain a highly conductive polymer solid electrolyte membrane.
[0015] Optionally, nano titanium dioxide particles are prepared according to the following method:
[0016] At 0℃-5℃, add 10±1% NH3·H2O solution dropwise into 30mL 0.8M TiOSO4 transparent solution, place on a magnetic stirrer and stir thoroughly until pH = 8±0.5, obtain a white precipitate, wash the precipitate several times with deionized water, and detect the supernatant with Ba(NO3)2 until no precipitate is produced to remove SO4 2- ; Pour the washed white precipitate into a three-necked flask, add 40mL 15% H2O2 solution to obtain a light yellow solution. Condensate and reflux at 98℃-100℃ for 48±2h, centrifuge and wash the precipitate, and dry at 80±5℃ to obtain white nano titanium dioxide particles.
[0017] Optionally, preparing nano-perovskite quantum dots includes preparing a perovskite precursor solution, including: taking cesium iodide and lead bromide, dissolving them in dimethyl sulfoxide, stirring at 60±2° C. for 30±5 min until the solution is completely clear without yellow precipitate, to obtain a perovskite precursor solution.
[0018] Optionally, after preparing the perovskite precursor solution, the method further includes: centrifuging the obtained perovskite precursor solution at a rotation speed of 5000rpm-7000rpm for 5min-7min, after centrifugation, pouring out the supernatant, collecting the precipitate at the bottom, dispersing the precipitate in n-hexane, adding an appropriate amount of ethyl acetate and centrifuging, repeating 3-4 times, placing the precipitate in a vacuum oven at 80°C-85°C, drying for 22h-24h, removing the organic solvent, obtaining the perovskite quantum dot powder, and placing it in a glove box for standby use.
[0019] On the other hand, the present invention provides the use of the above-mentioned perovskite-based positive electrode interface-stabilized solid electrolyte in the preparation of lithium batteries.
[0020] On the other hand, the present invention also provides a lithium battery, comprising the above-mentioned perovskite-based positive electrode interface-stabilized solid electrolyte.
[0021] Compared with the prior art, the perovskite-based positive electrode interface-stable solid electrolyte and its application, and lithium battery provided by the present invention achieve at least the following beneficial effects:
[0022] The present invention evenly disperses nano titanium dioxide particles and nano perovskite quantum dots in a PEO matrix, utilizes Lewis acid-base action and the size effect of ultrafine nanoparticles, effectively reduces the proportion of crystalline regions in the PEO system, and promotes the movement of PEO polymer segments.
[0023] In the present invention, the sizes of titanium dioxide particles and perovskite quantum dots are both nanometer-sized, and there will be no problem of agglomeration of doped filler particles in the polymer matrix resulting in a decrease in ion transmission performance due to the excessive size of the doped filler particles.
[0024] In terms of improving ion transport performance, the present invention utilizes the lithium affinity of active particles and the lithium sites inside them to form additional lithium ion transport channels, thereby improving the ion mobility of PEO-based polymer electrolytes. X I 3-X Perovskite quantum dots are unstable and will undergo a phase transition to an orthorhombic phase after being added to a PEO-lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution. This transition is attributed to the electrostatic adsorption of halogen anions on lithium ions, because halogen anions have strong Lewis base properties. In addition, TiO2 is an amphoteric oxide that can act as a bridge for the Lewis acid-base reaction between lithium salts and PEO, thereby promoting the dissociation of lithium salts and intensifying the movement of PEO chain segments. Therefore, when the content of nano-TiO2 in the active particles is high, the crystallization of PEO is also significantly inhibited, and it will further compete with the oxygen atoms in the PEO chain to absorb lithium ions. At the same time, nano-CsPbBr X I 3-X The addition of perovskite quantum dots will produce additional static and steric hindrance, promoting the dissociation of lithium salt anions, thereby releasing more free lithium ions and improving ion transport performance.
[0025] In terms of inhibiting the growth of lithium dendrites during battery cycling, nano-CsPbBr X I 3-X Perovskite quantum dots have a synergistic effect. On the one hand, nano-CsPbBr X I 3-X The cesium ions in the perovskite quantum dots, which have the same charge as the lithium ions, can exert an electrostatic shielding effect to delay the deposition of the remaining lithium ions and play a self-repairing role in smoothing the surface of the lithium metal anode. On the other hand, due to the strong Lewis base characteristics of the halogen anions, they have the potential to react with the lithium metal anode to form a LiX interface layer, which can reduce the Li + The activation barrier for transport at the electrolyte-electrode interface allows it to transport lithium ions in the plane, while its high Young's modulus can suppress the growth of lithium dendrites, thus ensuring long-term stable battery cycling.
[0026] The present invention mainly improves the performance of PEO-based polymer solid electrolyte by adding nanoparticles. The modified solid electrolyte combines the good mechanical properties of inorganic nano-titanium dioxide particles with the flexibility of the polymer. The addition of nanoparticles reduces the proportion of crystalline regions in PEO and improves the mobility of PEO chain segments, which can greatly improve the room temperature ionic conductivity and lithium ion migration number as well as the compatibility with lithium metal negative electrodes, and finally obtains a PEO-based polymer solid electrolyte with high conductivity.
[0027] Compared with the prior art, the perovskite-based positive electrode interface-stable solid electrolyte and its application, and lithium battery provided by the present invention achieve at least the following beneficial effects:
[0028] In terms of inhibiting the crystallinity of the polyethylene oxide matrix, the present invention evenly disperses nano titanium dioxide particles and nano perovskite quantum dots in the PEO matrix, utilizes Lewis acid-base action and the size effect of ultrafine nanoparticles, effectively reduces the proportion of the crystalline region in the PEO system, and promotes the movement of the PEO polymer chain segments. The sizes of the titanium dioxide particles and the perovskite quantum dots in the present invention are both nanometer-sized, and there will be no problem of agglomeration in the polymer matrix due to the excessive size of the doped filler particles, resulting in a decrease in ion transmission performance.
[0029] In terms of improving ion transport performance, the lithium affinity of active particles and the lithium sites inside them are used to form additional lithium ion transport channels to improve the ion mobility of PEO-based polymer electrolytes. X I 3-X Perovskite quantum dots are unstable and will undergo a phase transition to an orthorhombic phase after being added to a PEO-lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution. This transition is attributed to the electrostatic adsorption of halogen anions on lithium ions, because halogen anions have strong Lewis base properties. In addition, TiO2 is an amphoteric oxide that can act as a bridge for the Lewis acid-base reaction between lithium salts and PEO, thereby promoting the dissociation of lithium salts and intensifying the movement of PEO chain segments. Therefore, when the content of nano-TiO2 in the active particles is high, the crystallization of PEO is also significantly inhibited, and it will further compete with the oxygen atoms in the PEO chain to absorb lithium ions. At the same time, nano-CsPbBr X I 3-X The addition of perovskite quantum dots will produce additional static and steric hindrance, promoting the dissociation of lithium salt anions, thereby releasing more free lithium ions and improving ion transport performance.
[0030] In terms of inhibiting the growth of lithium dendrites during battery cycling, nano-CsPbBr X I 3-X Perovskite quantum dots have a synergistic effect. On the one hand, nano-CsPbBrX I 3-X The cesium ions in the perovskite quantum dots, which have the same charge as the lithium ions, can exert an electrostatic shielding effect to delay the deposition of the remaining lithium ions and play a self-repairing role in smoothing the surface of the lithium metal anode. On the other hand, due to the strong Lewis base characteristics of the halogen anions, they have the potential to react with the lithium metal anode to form a LiX interface layer, which can reduce the Li + The activation barrier for transport at the electrolyte-electrode interface allows it to transport lithium ions in the plane, while its high Young's modulus can suppress the growth of lithium dendrites, thus ensuring long-term stable battery cycling.
[0031] The present invention mainly improves the performance of PEO-based polymer solid electrolyte by adding nanoparticles. The modified solid electrolyte combines the good mechanical properties of inorganic nano-titanium dioxide particles with the flexibility of the polymer. The addition of nanoparticles reduces the proportion of crystalline regions in PEO and improves the mobility of PEO chain segments, which can greatly improve the room temperature ionic conductivity and lithium ion migration number as well as the compatibility with lithium metal negative electrodes, and finally obtains a PEO-based polymer solid electrolyte with high conductivity.
[0032] Of course, any product implementing the present invention does not necessarily need to achieve all of the technical effects described above at the same time.
[0033] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0035] Figure 1 It is a flow chart of a method for preparing a solid electrolyte with stable positive electrode interface based on perovskite;
[0036] Figure 2 This is a scan of perovskite quantum dots;
[0037] Figure 3 This is a scan of nano titanium dioxide particles;
[0038] Figure 4 is the ionic conductivity of the solid electrolyte membrane;
[0039] Figure 5 It is the impedance comparison of the undoped PEO battery before and after cycling;
[0040] Figure 6 , Figure 7 and Figure 8This is the impedance comparison of doped PEO batteries after cycling. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0042] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0043] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.
[0044] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0045] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0046] Embodiment 1:
[0047] This embodiment provides a solid electrolyte with stable positive electrode interface based on perovskite, including: PEO, lithium salt, nano titanium dioxide particles and nano perovskite quantum dots;
[0048] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide LiTFSI, and the mass ratio of LiTFSI to PEO is 1:3;
[0049] The dosage of nano titanium dioxide particles is 0.3% of the dosage of PEO;
[0050] The perovskite quantum dots are CsPbBr2I1, and the amount of CsPbBr2I1 is 1.0% of PEO.
[0051] Among various polymer solid electrolyte matrices, PEO has a special (-CH2-CH2-O-) nThe structure enables it to form metal complexes with many lithium salts, with high dielectric constant, low glass transition temperature, and strong donor properties of ether oxygen atoms, which helps dissolve lithium ions and is easy to manufacture. PEO is selected as the polymer matrix because PEO has relatively stable performance and good flexibility, and has better contact with the electrode; and LiTFSI as a lithium salt has the advantage that the anion diameter in its molecule is large, which can be confined around the PEO chain segment, forming an "anion fixation" effect, thereby further promoting the dissociation of lithium salts and improving the ion mobility of the entire system. TiO2 is an amphoteric oxide that can act as a bridge for the Lewis acid-base reaction between lithium salts and PEO, thereby promoting the dissociation of lithium salts and also intensifying the movement of PEO chain segments. Therefore, when the TiO2 content in the active particles is within a certain range, the crystallization of PEO is also significantly inhibited, and it will further compete with the oxygen atoms in the PEO chain to absorb lithium ions.
[0052] The size of titanium dioxide particles and perovskite quantum dots is nanometer-scale, so there will be no problem of agglomeration of doped filler particles in the polymer matrix leading to a decrease in ion transport performance due to the large size of the doped filler particles.
[0053] The dosage of nano titanium dioxide particles is 0.5%±0.2% of the dosage of PEO. Too much or too little ratio of nano titanium dioxide particles to PEO will affect the contact between the electrodes to a certain extent. In this embodiment, the dosage of nano titanium dioxide particles is 0.3% of the dosage of PEO, which will not affect the contact between the electrodes.
[0054] The perovskite quantum dots are CsPbBr2I1, and the amount of CsPbBr2I1 is 1.0% of PEO. It is understandable that if there is too much CsPbBr2I1, the quantum dots will agglomerate, and if there is too little CsPbBr2I1, the concentration is too low and the effect is very small. X I 3-X Perovskite nanomaterials, due to their quantum size effect, special semiconductor properties and excellent carrier transport properties, can provide more ion transport paths within the polymer solid electrolyte matrix, and can be flexibly dimensionally controlled to obtain more unique functions, thereby obtaining a composite polymer solid electrolyte with good performance to meet the needs of lithium metal batteries.
[0055] Lithium bis(trifluoromethanesulfonyl)imide builds a stable anion network in the electrolyte through its unique molecular configuration, which not only significantly reduces the viscosity of the solution, but also greatly improves the shuttle rate of lithium ions. This characteristic is directly converted into high efficiency in the battery charging and discharging process. In another embodiment of the present invention, the lithium salt used is lithium perchlorate, and the amount of lithium perchlorate used is equal to that of lithium bis(trifluoromethanesulfonyl)imide, and the effect is the same, which is not specifically limited here.
[0056] This embodiment also provides a method for preparing a solid electrolyte with stable positive electrode interface based on perovskite, Figure 1 The preparation method of this embodiment comprises the following steps:
[0057] Step S101, preparing nano titanium dioxide particles;
[0058] At 0°C, add 10% NH3·H2O solution dropwise into 30 mL 0.8 M TiOSO4 transparent solution, place on a magnetic stirrer and stir thoroughly until pH = 8 to obtain a white precipitate. 4 Wash the precipitate several times with deionized water by centrifugation, and test the supernatant with Ba(NO3)2 until no precipitate is produced to remove SO4 2- The washed white precipitate was poured into a three-necked flask, and 40 mL of 15% H2O2 solution was added to obtain a light yellow solution. The solution was condensed and refluxed at 100°C for 48 h, and the precipitate was washed by centrifugation and dried at 80°C to obtain white nano titanium dioxide particles.
[0059] The morphology of the prepared nano-TiO2 was characterized, and the scanning electron microscope image is shown in Figure 3 .Depend on Figure 3 It can be seen that nano-sized TiO2 has a very uniform distribution and uniform size, with an average size of about 10 nanometers, showing a high degree of monodispersity and no obvious agglomeration. Step S102, preparing CsPbBr2I1 perovskite quantum dots
[0060] Preparation of perovskite precursor solution: Take the perovskite precursor material and dissolve it in dimethyl sulfoxide to prepare a perovskite precursor solution. Since this section requires the preparation of perovskite solutions of different proportions, the CsPbBr2I1 perovskite solution is used as an example. Take 0.6mmol cesium iodide (CsI) and 0.6mmol lead bromide (PbBr2), dissolve them in 0.5ml of dimethyl sulfoxide, stir at 60℃ for 3h to obtain a CsPbBr2I1 perovskite precursor solution with a concentration of 1.2mmol / ml, see Figure 2 .
[0061] The obtained perovskite precursor solution was centrifuged at 6000 rpm for 5 minutes. After centrifugation, the supernatant was poured out, the precipitate at the bottom was collected and dispersed in n-hexane, and then an appropriate amount of ethyl acetate was added for centrifugation. This process was repeated three times, and the precipitate was placed in a vacuum oven at 80°C and dried for 24 hours to remove the organic solvent, and the perovskite quantum dot powder was obtained and placed in a glove box for use.
[0062] It should be noted that the order of the above steps S1 and S2 can be swapped, and no specific limitation is made here.
[0063] Step S103, preparing a highly conductive polymer solid electrolyte membrane
[0064] PEO (weight average molecular weight Mw = 60w) and LiTFSI are added to an appropriate amount of acetonitrile in a mass ratio of EO:Li = 16:1, and stirred with a magnetic stirrer for more than 5 hours to obtain a uniform polymer solution. A constant temperature magnetic stirrer is used to stir at 60°C, and the dried nano-TiO2 particles and nano-CsPbBr2I1 perovskite quantum dots are added to the above solution, and heating and stirring are continued for 24 hours to fully dissolve the solution to obtain a uniform slurry. Finally, the homogeneous suspension is poured into a polytetrafluoroethylene mold to form a film. After ensuring that the solvent is completely volatilized, the electrolyte membrane is transferred to a vacuum oven and vacuum dried for 12 hours to obtain a uniformly dried composite electrolyte membrane (i.e., a highly conductive polymer solid electrolyte membrane).
[0065] Embodiment 2:
[0066] This embodiment provides a solid electrolyte with stable positive electrode interface based on perovskite, including: PEO, lithium salt, nano titanium dioxide particles and nano perovskite quantum dots;
[0067] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide LiTFSI, and the mass ratio of LiTFSI to PEO is 1:1;
[0068] The dosage of nano titanium dioxide particles is 0.7% of the dosage of PEO;
[0069] Perovskite quantum dots are CsPbBr 1.5 I 1.5 , CsPbBr 1.5 I 1.5 The dosage is 1.1% of PEO.
[0070] The method for preparing a perovskite-based positive electrode interface-stable solid electrolyte provided in this embodiment comprises the following steps:
[0071] Step S201, preparing nano titanium dioxide particles:
[0072] At 3°C, add 11% NH3·H2O solution dropwise into 30mL 0.8M TiOSO4 transparent solution, place on a magnetic stirrer and stir thoroughly until pH = 7.8, and obtain a white precipitate. Wash the precipitate several times with deionized water by centrifugation, and detect the supernatant with Ba(NO3)2 until no precipitate is produced to remove SO4. 2- The washed white precipitate was poured into a three-necked flask, and 41 mL of 15% H2O2 solution was added to obtain a light yellow solution. The solution was condensed and refluxed at 99°C for 49 h, and the precipitate was washed by centrifugation and dried at 82°C to obtain white nano titanium dioxide particles.
[0073] Step S202, preparing CsPbBr 1.5 I 1.5 Perovskite quantum dots:
[0074] Preparation of perovskite precursor solution: Take a certain amount of perovskite precursor material and dissolve it in dimethyl sulfoxide to prepare a perovskite precursor solution. Since this part requires the preparation of perovskite solutions of different proportions, CsPbBr 1.5 I 1.5 Take the perovskite solution as an example. Take 1.5mmol of cesium iodide (CsI) and 0.75mmol of lead bromide (PbBr2), dissolve them in 0.5ml of dimethyl sulfoxide, and stir at 60℃ for 35min to obtain CsPbBr 1.5 I 1.5 Perovskite precursor solution.
[0075] The obtained CsPbBr 1.5 I 1.5 The perovskite precursor solution was centrifuged at 7000 rpm for 5 minutes. After centrifugation, the supernatant was poured off, the precipitate at the bottom was collected and dispersed in n-hexane, and then an appropriate amount of ethyl acetate was added for centrifugation. This process was repeated three times, and the precipitate was placed in a vacuum oven at 80°C and dried for 24 hours to remove the organic solvent, and the perovskite quantum dot powder was obtained and placed in a glove box for later use.
[0076] Step S203, preparing a highly conductive polymer solid electrolyte membrane
[0077] PEO (weight average molecular weight Mw = 60w) and LiTFSI were added to an appropriate amount of acetonitrile in a mass ratio of EO:Li = 16:1, and stirred with a magnetic stirrer for more than 5 hours to obtain a uniform polymer solution. A constant temperature magnetic stirrer was used to stir at 60°C, and the dried nano-TiO2 particles and nano-CsPbBr 1.5 I 1.5 Perovskite quantum dots are added to the above solution, and heating and stirring are continued for 24 hours to fully dissolve the solution to obtain a uniform slurry. Finally, the homogeneous suspension is poured into a polytetrafluoroethylene mold to form a film. After ensuring that the solvent is completely evaporated, the electrolyte membrane is transferred to a vacuum oven and vacuum dried for 12 hours to obtain a uniformly dried composite electrolyte membrane (highly conductive polymer solid electrolyte membrane).
[0078] Embodiment 3:
[0079] This embodiment provides a solid electrolyte with stable positive electrode interface based on perovskite, including: PEO, lithium salt, nano titanium dioxide particles and nano perovskite quantum dots; wherein,
[0080] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and the mass ratio of LiTFSI to PEO is 1:4;
[0081] The dosage of nano titanium dioxide particles is 0.5% of the dosage of PEO;
[0082] Perovskite quantum dots are CsPbBr 2.5 I 0.5 , CsPbBr 2.5 I 0.5 The dosage is 0.9% of PEO.
[0083] This embodiment provides a method for preparing a solid electrolyte with stable positive electrode interface based on perovskite, comprising the following steps:
[0084] Step S301, preparing nano titanium dioxide particles:
[0085] At 0°C, add 10% NH3·H2O solution dropwise into 30 mL 0.8 M TiOSO4 transparent solution, place on a magnetic stirrer and stir thoroughly until pH = 8 to obtain a white precipitate. 4 Wash the precipitate several times with deionized water by centrifugation, and test the supernatant with Ba(NO3)2 until no precipitate is produced to remove SO4 2- The washed white precipitate was poured into a three-necked flask, and 40 mL of 15% H2O2 solution was added to obtain a light yellow solution. The solution was condensed and refluxed at 100°C for 48 h, and the precipitate was washed by centrifugation and dried at 80°C to obtain white nano titanium dioxide particles.
[0086] Step S302, preparing CsPbBr 2.5 I 0.5 Perovskite quantum dots:
[0087] Preparation of perovskite precursor solution: Take a certain amount of perovskite precursor material and dissolve it in dimethyl sulfoxide to prepare a perovskite precursor solution. Since this part requires the preparation of perovskite solutions of different proportions, CsPbBr 2.5 I 0.5 Take the perovskite solution as an example. Take 0.6mmol cesium iodide (CsI), 0.6mmol lead iodide (PbI2) and 0.75mmol lead bromide (PbBr2), dissolve them in 0.5ml dimethyl sulfoxide, stir at 60℃ for 3h to obtain CsPbBr2 with a concentration of 1.2mmol / ml. 2.5 I 0.5 Perovskite precursor solution.
[0088] The obtained perovskite precursor solution was centrifuged at 8000 rpm for 4.3 minutes. After centrifugation, the supernatant was poured out, the precipitate at the bottom was collected and dispersed in n-hexane, and then an appropriate amount of ethyl acetate was added for centrifugation. This process was repeated three times, and the precipitate was placed in a vacuum oven at 80°C and dried for 24 hours to remove the organic solvent, and the perovskite quantum dot powder was obtained and placed in a glove box for use.
[0089] Step S303: preparing a highly conductive polymer solid electrolyte membrane
[0090] PEO (Mw = 60w) and LiTFSI were added to an appropriate amount of acetonitrile in a ratio of EO:Li = 16:1, and a uniform polymer solution was obtained by stirring with a magnetic stirrer for more than 5 hours. A constant temperature magnetic stirrer was used to stir at 60°C, and the dried nano-TiO2 particles and nano-CsPbBr 2.5 I 0.5 Perovskite quantum dots are added to the above solution, and heating and stirring are continued for 24 hours to fully dissolve the solution to obtain a uniform slurry. Finally, the homogeneous suspension is poured into a polytetrafluoroethylene mold to form a film. After ensuring that the solvent is completely evaporated, the electrolyte membrane is transferred to a vacuum oven and vacuum dried for 12 hours to obtain a uniformly dried composite electrolyte membrane (highly conductive polymer solid electrolyte membrane).
[0091] Comparative Example 1:
[0092] The difference between Comparative Example 1 and Example 1 is that only PEO+LiTFSI is used to make the electrolyte membrane, and the comparative example 1 is not doped with nano titanium dioxide particles and nano perovskite quantum dots, and there is no step S1 and step S2 in the production process.
[0093] The preparation method is as follows: PEO (weight average molecular weight Mw = 60w) and LiTFSI are added to an appropriate amount of acetonitrile in a mass ratio of EO:Li = 16:1, and a uniform polymer solution is obtained by stirring with a magnetic stirrer for more than 5 hours. A constant temperature magnetic stirrer is used to stir at 60°C, and heating and stirring are continued for 24 hours to fully dissolve the solution to obtain a uniform slurry. Finally, the homogeneous suspension is poured into a polytetrafluoroethylene mold to form a film. After ensuring that the solvent is completely volatilized, the electrolyte membrane is transferred to a vacuum oven and vacuum dried for 12 hours to obtain a uniformly dried electrolyte membrane.
[0094] The composite electrolyte membrane prepared in Example 1 was assembled into button cells and the following performance tests were performed:
[0095] (1) Characterization of synthetic materials
[0096] Figure 3 This is the SEM image of synthesized nano-sized TiO2, showing a spindle-shaped structure with a long rice grain shape, good dispersion and a particle size ranging from about 20nm to 30nm.
[0097] (2) Ionic conductivity and impedance test
[0098] In order to verify the feasibility of PEO+TiO2+CsPbBr2I1 polymer solid electrolyte in all-solid-state lithium metal batteries, an all-solid-state lithium metal battery was assembled with lithium metal as the negative electrode, LiFePO4 as the positive electrode, and PEO+TiO2+CsPbBr2I1 as the polymer solid electrolyte (because it has the best electrochemical properties mentioned above), and its rate performance and cycle stability were tested. All full battery performances were tested at 90°C, because as the temperature increases, the melting and penetration of the PEO matrix will form excellent interface contact, providing a fast lithium ion transfer channel, so that the all-solid-state lithium metal battery has efficient cycle and rate performance. The electrochemical workstation was used for AC impedance spectroscopy testing. Then the following formula was used for calculation:
[0099]
[0100] Wherein, σ is the ionic conductivity, L is the thickness of the electrolyte membrane, R is the measured resistance, and S is the area of the electrolyte membrane.
[0101] Test results such as Figure 4 As shown, Figure 4 The middle curve includes blank PEO, PEO filled with TiO2, and PEO, TiO2 and different proportions of nano-perovskite quantum dots. Here, TiO2 refers to nano-titanium dioxide particles. The curves from top to bottom are PEO+TiO2+CsPbBr2I1, PEO+TiO2+CsPbBr 1.5 I 1.5 、PEO+TiO2+CsPbBr 2.5 I 0.5 , PEO+TiO2, PEO, the ionic conductivity is lowest when there is no TiO2 and no perovskite quantum dots. Figure 4 It can be seen that at 30°C, when PEO+TiO2+CsPbBr2I1 is doped, the ionic conductivity of the electrolyte membrane can reach 3×10 -4 S cm -1 .
[0102] Reference Figure 5 The impedance comparison of the undoped PEO battery before and after cycling shows that the interface resistance of the undoped PEO lithium metal battery increases significantly from about 1000Ω to 2000Ω after cycling. Figure 6 , impedance comparison of PEO battery after cycling after doping, PEO+TiO2+CsPbBr 1.5 I 1.5 The interfacial resistance of lithium metal batteries has hardly increased significantly ( Figure 6), indicating that during the battery cycle, PEO+TiO2+CsPbBr 1.5 I 1.5 A more stable interface is formed between the polymer solid electrolyte and the positive and negative electrodes, ensuring the long-term, efficient and stable operation of the battery. Figure 7 , the impedance comparison of the PEO battery after cycling after doping, the interface resistance of the PEO+TiO2+CsPbBr2I1 lithium metal battery has almost no obvious increase ( Figure 7 ), indicating that a more stable interface is formed between the PEO+TiO2+CsPbBr2I1 polymer solid electrolyte and the positive and negative electrodes during the battery cycle, ensuring the long-term, efficient and stable operation of the battery. Figure 8 , impedance comparison of PEO battery after cycling after doping, PEO+TiO2+CsPbBr 2.5 I 0.5 The interfacial resistance of lithium metal batteries changes little ( Figure 8 ), indicating that during the battery cycle, PEO+TiO2+CsPbBr 2.5 I 0.5 A more stable interface is formed between the polymer solid electrolyte and the positive and negative electrodes, ensuring long-term, efficient and stable operation of the battery.
[0103] (3) Determination of lithium ion migration number and tensile strength
[0104] First, the polymer electrolyte membrane and two metal lithium sheets are assembled into a metal lithium symmetric battery. Ionic conductivity: At 25°C, a 10mm diameter cylindrical stainless steel current collector is used in the battery mold to tightly clamp the solid electrolyte membrane under mechanical pressure, and then the current collector is connected to the electrochemical workstation. The solid electrolyte membrane is subjected to electrochemical impedance test at a bias voltage of 10mV and a frequency range of 106Hz to 0.1Hz. Tensile strength: The samples obtained in the embodiments and comparative examples are cut into long strip specimens with a width of 25mm and a length of not less than 150mm. The initial distance between the clamps is set to 100±5mm. The two ends of the sample are placed in the upper and lower ends of the clamp in turn, and the clamp is clamped. During the process, the sample and the clamp are ensured to be in the same vertical direction, and the force is uniform, without obvious tensile deformation. After the preparation is completed, the tensile strength test is carried out at a rate of 250±10mm / min.
[0105] Table 1 Lithium ion migration number and tensile strength test
[0106] Lithium ion migration number <![CDATA[Tensile strength (Kgf / cm 2 )]]> Example 1 0.62 1935 Example 2 0.52 1860 Example 3 0.46 1720 Comparative Example 1 0.18 1810
[0107] It can be concluded from Table 1 that PEO+TiO2+CsPbBr2I1, PEO+TiO2+CsPbBr 1.5 I 1.5 、PEO+TiO2+CsPbBr2.5 I 0.5 After the combination, the lithium ion migration number is significantly improved, which is greater than the lithium ion migration number without doping. This shows that doping nano-titanium dioxide particles and nano-perovskite quantum dots helps the rapid conduction of lithium ions between the positive and negative electrodes on both sides of the electrolyte, increases the rate of positive and negative electrode reactions, reduces the concentration polarization inside the battery, and enables the battery to operate at a high current density, thereby improving the battery's discharge capacity and cycle stability.
[0108] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A solid electrolyte with a stable positive electrode interface based on perovskite, characterized in that: include: Polyethylene oxide, lithium salt, nano-titanium dioxide particles and nano-perovskite quantum dots, wherein the nano-titanium dioxide particles modify the polyethylene oxide; The dosage of the nano titanium dioxide particles is 0.3%-0.7% of the dosage of the polyethylene oxide.
2. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 1, characterized in that: The lithium salt includes lithium bis(trifluoromethanesulfonyl)imide or lithium perchlorate, and the mass ratio of the lithium salt to the polyethylene oxide is 1:1-1:
4.
3. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 1, characterized in that: The nano perovskite quantum dots include CsPbBr X I 3-X , where X is greater than 0 and less than 3.
4. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 1, characterized in that: The dosage of the nano-perovskite quantum dots is 1.0%±0.1% of the polyethylene oxide.
5. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 1, characterized in that: The perovskite-based positive electrode interface-stable solid electrolyte is prepared according to the following method, including: preparing nano titanium dioxide particles; Preparation of nano-perovskite quantum dots; The method comprises the steps of adding the polyethylene oxide powder to a solution containing a lithium salt, and then sequentially adding the nano-perovskite quantum dots and the nano-titanium dioxide particles, heating and stirring at 60±5° C. for 24±2 h to obtain a uniform slurry, placing the slurry in a mold to form a film, removing the solvent, and vacuum drying to obtain a highly conductive polymer solid electrolyte membrane.
6. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 5, characterized in that: The nano titanium dioxide particles are prepared according to the following method: At 0℃-5℃, add 10±1% NH3·H2O solution dropwise into 30mL 0.8M TiOSO4 transparent solution, place on a magnetic stirrer and stir thoroughly until the pH is 8±0.5 to obtain a white precipitate. Wash the precipitate several times with deionized water by centrifugation, and detect the supernatant with Ba(NO3)2 until no precipitate is produced to remove SO4. 2- ; Pour the washed white precipitate into a three-necked flask, add 40±2mL of 15% H2O2 solution to obtain a light yellow solution, condense and reflux at 98℃-100℃ for 48±2h, centrifuge and wash the precipitate, and dry at 80±5℃ to obtain white nano titanium dioxide particles.
7. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 5, characterized in that: The preparation of nano-perovskite quantum dots includes preparing a perovskite precursor solution, including: taking cesium iodide and lead bromide, dissolving them in dimethyl sulfoxide, stirring at 60±2° C. for 30±5 minutes until the solution is completely clear without yellow precipitate, to prepare a perovskite precursor solution.
8. The perovskite-based positive electrode interface-stable solid electrolyte according to claim 7, characterized in that: After preparing the perovskite precursor solution, the following steps are also included: The obtained perovskite precursor solution is centrifuged at a speed of 5000rpm-7000rpm for 5min-7min. After centrifugation, the supernatant is poured out, the precipitate at the bottom is collected, and the precipitate is dispersed in n-hexane. An appropriate amount of ethyl acetate is added and centrifuged. This is repeated 3-4 times. The precipitate is placed in a vacuum oven at 80°C-85°C and dried for 22h-24h. The organic solvent is removed to obtain the perovskite quantum dot powder, which is placed in a glove box for later use.
9. Use of a perovskite-based positive electrode interface-stable solid electrolyte according to any one of claims 1 to 8 in the preparation of a lithium battery.
10. A lithium battery, characterized in that: A solid electrolyte with stable positive electrode interface based on perovskite as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Modification method of polymer solid polyelectrolyte
CN112864469A
Composite solid electrolyte membrane based on surface defect titanium dioxide as well as preparation method and application of composite solid electrolyte membrane
CN113206288A
Composite solid electrolyte and preparation method and application thereof
CN113346129A
High-conductivity polymer solid electrolyte and preparation method thereof
CN113394464A
Ceramic composite solid electrolyte containing inorganic nano oxide particles, and preparation method and application thereof
CN114976215A